Ideas for Extending the Approach to Evaluating Health in All Policies in South Australia; Comment on "Developing a Framework for a Program Theory-Based Approach to Evaluating Policy Processes and Outcomes: Health in All Policies in South Australia" - Ketan Shankardass; Patricia O'Campo; Carles Muntaner; Ahmed M. Bayoumi; Lauri Kokkinen (Kerman University of Medical Sciences, 2018)
Since 2008, the government of South Australia has been using a Health in All Policies (HiAP) approach to achieve their strategic plan (South Australia Strategic Plan of 2004). In this commentary, we summarize some of the strengths and contributions of the innovative evaluation framework that was developed by an embedded team of academic researchers. To inform how the use of HiAP is evaluated more generally, we also describe several ideas for extending their approach, including: deeper integration of interdisciplinary theory (eg, public health sciences, policy and political sciences) to make use of existing knowledge and ideas about how and why HiAP works; including a focus on implementation outcomes and using developmental evaluation (DE) partnerships to strengthen the use of HiAP over time; use of systems theory to help understand the complexity of social systems and changing contexts involved in using HiAP; integrating economic considerations into HiAP evaluations to better understand the health, social and economic benefits and trade-offs of using HiAP.